The Inhibitory Effect of Some Medical Plants Extracts In The Fungus Aspergillus fumigatus - Shifaa Jaafer; Abdulkarim Al-Nuaymi; Saleh Mohammed (College of Education for Pure Sciences, 2020)
Study the inhibitory effect of aqueous and alcoholic extract of four medical plants: Mentha longifolia, Mentha spicata, Cyperus  rotundus and Nigella sativa (black cumin) against some human pathogenic fungi isolated from different clinical cases, showed that (4) from 14 cases gave positive effect on Aspergillus fumigatus bythe frequency 16.67%   Studying the inhibitory effect of aqueous extract against the isolated fungi, showed that aqueous extract of black sead at conc. 30 mg/ml was the best one, which inhibited the growth of A. fumigatus by 87.5%.      Alcoholic extracts of black cumin (10 mg/ml), spearmint (15 mg/ml)and horsemint (30 mg/ml) were more effective against A. fumigatus, and inhibited the growth of A.fumigatus completely. Testing some chemical antifungals against the isolated fungus showed that ketoconazole at concentration (3.5 , 3.0 , 2.5 mg/ml) inhibited the growth by the ratio of 100%, 93.0% and 90. 0 % respectively.